1977
DOI: 10.1128/jb.130.2.746-749.1977
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Saccharomyces cerevisiae glycolytic pathway mutants

Abstract: Yeast strains carrying recessive mutations representing four different loci that cause defects in pyruvate kinase, pyruvate decarboxylase, 3-phosphoglycerate kinase, and 3-phosphoglycerate mutase were isolated and partially characterized. Cells carrying these mutations were unable to use glucose as a carbon source as measured in turbidimetric growth experiments. Tetrad analysis indicated that these mutations were not linked to each other; one of the mutations, that affecting phosphoglycerate kinase, was locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The transcriptome analysis performed in this study indicates that the severely impaired growth phenotype of the Δgpm1 strain is associated with a global stress response.As it has been previously shown [3,4], a Δgpm1 strain is incapable of growing on glucose as the sole carbon source but growth can be restored in presence of a mixture of glycerol and ethanol (2-3% v/v). Previous studies [1] have suggested that ethanol is respired whereas glycerol is needed to feed gluconeogenesis.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The transcriptome analysis performed in this study indicates that the severely impaired growth phenotype of the Δgpm1 strain is associated with a global stress response.As it has been previously shown [3,4], a Δgpm1 strain is incapable of growing on glucose as the sole carbon source but growth can be restored in presence of a mixture of glycerol and ethanol (2-3% v/v). Previous studies [1] have suggested that ethanol is respired whereas glycerol is needed to feed gluconeogenesis.…”
Section: Discussionmentioning
confidence: 86%
“…It was previously shown that a S. cerevisiae strain deleted in the glycolytic gene GPM1 (encoding phosphoglycerate mutase) is not able to use glucose as sole carbon source but has the capability to grow on a mixture of ethanol and glycerol [4]. Here we studied the physiological response of a Δgpm1 strain in batch cultivations in minimal media supplemented with glycerol (3% v/v) and ethanol 2.5% (v/v) as carbon sources.…”
Section: Physiological Characterization Of the Deletion Strain δ δGpmmentioning
confidence: 99%
See 2 more Smart Citations
“…Several yeast glycolytic mutants have been isolated recently (3,7,14,15,23), but only mutants lacking hexokinases (16), phosphoglucose isomerase (18), or pyruvate kinase (20,23) were characterized in detail. The common feature of all of those mutants was that growth was inhibited by glucose.…”
mentioning
confidence: 99%